An angle-changeable tracked robot with human-robot interaction in unstructured environments. Issue 4 (17th April 2020) - Zong, Chengguo; Ji, Zhijian; Yu, Junzhi; Yu, Haisheng
Abstract : Purpose: The purpose of this paper is to study the adaptability of the tracked robot in complex working environment. It proposes an angle-changeable tracked robot with human–robot interaction in unstructured environment. The study aims to present the mechanical structure and human–robot interaction control system of the tracked robot and analyze the static stability of the robot working in three terrains, i.e. rugged terrain, sloped terrain and stairs. Design/methodology/approach: The paper presents the mechanical structure and human–robot interaction control system of the tracked robot. To prevent the detachment of the tracks during obstacle navigation, a new type of passively adaptive device based on the relationship between the track's variable angle and the forces is presented. Then three types of rough terrain are chosen to analyze the static stability of the tracked robot, i.e. rugged terrain, sloped terrain and stairs. Findings: This paper provides the design method of the tracked robot. Owing to its appropriate dimensions, good mass distribution and limited velocity, the tracked robot remains stable on the complex terrains. The experimental results verify the effectiveness of the design method. Originality/value: The theoretical analysis of this paper provides basic reference for the structural design of tracked robots.